2019 IEEE/CVF International Conference on Computer Vision (ICCV) 2019
DOI: 10.1109/iccv.2019.00420
|View full text |Cite
|
Sign up to set email alerts
|

Multi-View Image Fusion

Abstract: Figure 1: We present a method for multi-view image fusion that is a applicable to a variety of scenarios: a higher resolution monochrome image is colorized with a second color image (top row), two color images with different exposures are fused into an HDR lower-noise image (middle row), and a high quality DSLR image is warped to the lower quality stereo views captured by a VR-camera (bottom row).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 26 publications
(30 reference statements)
0
12
0
Order By: Relevance
“…Trinidad et al (2019) suggested three cases for image fusion which are colour conversion for the colour inferences on the monochrome display, HDR fusion to merge malaligned brake exposure and data transfer from a cost-beneficial camera in order to reproject a high-definition image [6].…”
Section: Methods Of Image Fusionmentioning
confidence: 99%
“…Trinidad et al (2019) suggested three cases for image fusion which are colour conversion for the colour inferences on the monochrome display, HDR fusion to merge malaligned brake exposure and data transfer from a cost-beneficial camera in order to reproject a high-definition image [6].…”
Section: Methods Of Image Fusionmentioning
confidence: 99%
“…To overcome the problem of relative movements between pixels, dense correspondence searching and alignment subnets are integrated into the CNN models, e.g. (Kalantari and Ramomoorthi 2017) (Chen et al 2020) (Trinidad et al 2019), to improve the reconstruction quality. Since the alignment results may not be perfect all the time, some recent works, e.g.…”
Section: Related Workmentioning
confidence: 99%
“…3). Multi-view image fusion [62] was proposed to fuse misaligned photos from different camera sensors. It can transfer details from a highquality DSLR image to images taken by a VR180 camera [63].…”
Section: General Scenesmentioning
confidence: 99%